Geographical Economic Concentration, Growth and Decentralization: Empirical Evidence in Aceh, Indonesia - Abd. Jamal (Muhammadiyah University Press, 2017)
This study aims to analyze the geographical economic concentration (GEC) in Aceh Province. The Decomposition AGC Index and secondary data for the period 2001-2013 are used in the analysis. The results showed that the GEC in Aceh Province tend to decline about -7.09 percents a year. But, since 2011 the growth increased about 1.27 percent a year. It showed five phases of changes of GEC. When the Aceh Province was proliferated from 13 to 23 districts, economic growth was not driving factor for economic concentration, but as a driving for de-concentration. Government spending density is significant for economic concentration driver, both in the period 2001-2007, and 2008-2013. Government spending per capita is the driven factor for economic concentration during the period 2008-2013. As well in Aceh-13 (period 2001-2013). This suggests that direct government expenditure to be important in developing the center of economic growth in Aceh Province.